2015
DOI: 10.1096/fj.14-265801
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of glyceraldehyde 3‐phosphate dehydrogenase prevents neurovascular degeneration after retinal injury

Abstract: Ischemia and reperfusion (I/R) injury is a common cause of many vascular and neuronal diseases. Glyceraldehyde 3-phosphate dehydrogenase (GAPDH) has been found down-regulated or dysfunctional in several tissues upon I/R injury. To investigate the role of GAPDH in retinal I/R injury-induced neurovascular degeneration, the injured retinas of GAPDH transgenic (Tg) mice and wild-type (WT) littermates were analyzed. I/R injury induced neurovascular degeneration, energy failure, DNA damage, and necroptosis in the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 51 publications
5
23
0
Order By: Relevance
“…Moreover, our previous studies demonstrated that H4K20me1/me2 were significantly increased after retinal I/R 18 , as well as increased DNA damage response1822. Thus, we verified whether the increased H4K20me1 was also associated with increased activity of the DNA damage response in the retinas of diabetic rats.…”
Section: Resultssupporting
confidence: 74%
“…Moreover, our previous studies demonstrated that H4K20me1/me2 were significantly increased after retinal I/R 18 , as well as increased DNA damage response1822. Thus, we verified whether the increased H4K20me1 was also associated with increased activity of the DNA damage response in the retinas of diabetic rats.…”
Section: Resultssupporting
confidence: 74%
“…GAPDH is implicated in numerous cell functions; however, its role in cell death remains controversial and poorly understood (36). Whereas some reports indicate a proapoptotic function for GAPDH (37-39), others demonstrated a protective role (40)(41)(42)(43). The current paradigm considers GAPDH as a master switch in the regulation of cell death (44).…”
Section: Discussionmentioning
confidence: 99%
“…For immunofluorescence staining, primary antibody against PDGFRα (AF1062, 1:200 dilution, R&D Systems) or Ki67 (sc15402, 1:100 dilution, Santa Cruz) was applied overnight. The sections were then incubated with anti‐goat or anti‐rabbit secondary antibody followed by DAPI staining, and images were taken . The number of cells with positive staining for both Ki67 and PDGFRα per field was determined.…”
Section: Methodsmentioning
confidence: 99%